Development of technology for obtaining composite polymeric materials and antifriction-wear-resistant properties of the crutiums based on them - M.M. Sadiova (Zien Journals, 2022)
The article provides a literary review of studies that the best physical, mechanical and tribological properties when interacting with raw cotton have composite thermoset polymer materials filled with organomineral fillers, which is associated with improving the conditions for contact interaction by increasing the strength electro- and thermophysical properties of the composition
Keywords: machine; mechanism; part; friction